Usability Development for a Marine SO2 Scrubber - Westman, Daniel (My University, 2013)
This thesis has been a study of usability practices and HMI design made for the Ecotech department at Wärtsilä Finland Oy. The reasons for focusing on these have been clarified after which the most important literature on the subject is presented from a few different points of view of usability and HMI designing. These points of view being the process interface approach, a general software interface approach and lastly the human physiological limitations. Presenting principles for achieving good usability and HMI has been the purpose of the first section of the thesis and these have later been used for the implementation into the first commercial marine scrubber project delivered by Wärtsilä Finland Oy. The second aspect of the thesis is the development of reporting guidelines that are primarily based on legislation and usability practices are only used in applicable areas. The study guides us how to make them an easily accessable and clear part of the HMI and have to comply with regulations set by the International Maritime Organization. The practical part of the thesis goes through the process of defining users and access levels and from there specifying the interface and also what affects the usability studies have had on the automation software. Each view of the HMI is presented and the reasoning behind certain solutions is clarified. The final part of the thesis is HMI testing and evaluation and aims to verify what went well and what needs to be improved in the future. Potential testing methods by HMI researchers are presented and some are utilised in order to guide the future in Wärtsilä Ecotech HMI development.
Keywords: Sulphur scrubber; usability; HMI; fi=Automaatiotekniikka|en=Automation Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|